Comportamiento de las plantas de Lycopersicon esculentum mill "tomate" var. Regional en sustratos elaborados a partir de lombricompost y gallinaza en Zungarococha - Loreto - Rojas Castañeda, Fernando (2014)
The present investigation was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in areas of the Bovine Project located in the Fundo de Zungarococha, entitled Behavior of Lycopersicon esculentum MILL "tomate" Var. Regional in substrates made from vermicompost and chicken manure in Zungarococha - Loreto. The evaluations were carried out 76 days after the transplant, sown with botanical seeds, in plots of 5 m x 1 m (5 m2) and an experimental area of 126.5 m2. With a Complete Random Design (D.C.A) design, with four treatments and four repetitions, the treatments under study were: T0 (6 kilos of vermicompost), T1 (5.7 kilos of vermicompost + 300 grams of chicken manure), T2 (5.4 kilos of vermicompost + 600 grams of chicken manure) and T3 (5.1 kilos of vermicompost + 900 grams of chicken manure), obtaining the following results: That vermicompost plus 15% of chicken manure can be used as a substrate without causing damage to the Lycopersicon plant esculentum WILL. Tomato Var. Regional. That the contribution of chicken manure in a proportion of 15% to the vermicompost increases the yield of the fruits of the Lycopersicon esculentum WILL crop. Tomato Var. Regional. The maximum yield obtained in the cultivation of Lycopersicon esculentum WILL. Tomato Var. Regional, it was in the T3 treatment (5.1 kg of vermicompost + 900 gr of chicken manure), in plant height with 90.16 cm, diameter of the fruits of 4.19 cm, an average fruit weight of 0.83 kg, the number of plants I get 29 units. That this represents 15% chicken manure in 85% vermicompost. The yield shown in table 16 indicates that 102,000 kilos of vermicompost and 18,000 kilos of chicken manure will be needed to produce 16,400 kilos of regional tomato fruits per hectare taking the T3 treatment (5.1 kg of vermicompost + 900 gr of chicken manure), concluding that the amount of vermicompost is high and can only be produced in small areas such as organic gardens.